Ni and Co Segregations on Selective Surface Facets and Rational Design of Layered Lithium Transition‐Metal Oxide Cathodes. Issue 9 (5th February 2016) - Yan, Pengfei; Zheng, Jianming; Zheng, Jiaxin; Wang, Zhiguo; Teng, Gaofeng; Kuppan, Saravanan; Xiao, Jie; Chen, Guoying; Pan, Feng; Zhang, Ji‐Guang; Wang, Chong‐Min
Abstract : The chemical processes occurring on the surface of cathode materials during battery cycling play a crucial role in determining battery's performance. However, the understanding of such surface chemistry is far from clear due to the complexity of redox chemistry during battery charge/discharge. Through intensive aberration corrected STEM investigation on ten layered oxide cathode materials, two important findings on the pristine oxides are reported. First, Ni and Co show strong plane selectivity when building up their respective surface segregation layers (SSLs). Specifically, Ni‐SSL is exclusively developed on (200)m facet in Li–Mn‐rich oxides (monoclinic C2/m symmetry) and on (012)h facet in Mn–Ni equally rich oxides (hexagonal R‐3m symmetry), while Co‐SSL has a strong preference to (20−2)m plane with minimal Co‐SSL also developed on some other planes in Li–Mn‐rich cathodes. Structurally, Ni‐SSLs tend to form spinel‐like lattice while Co‐SSLs are in a rock‐salt‐like structure. Second, by increasing Ni concentration in these layered oxides, Ni and Co SSLs can be suppressed and even eliminated. The findings indicate that Ni and Co SSLs are tunable through controlling particle morphology and oxide composition, which opens up a new way for future rational design and synthesis of cathode materials. Abstract : For pristine Li–Mn‐rich oxide cathodes, Ni and Co show distinctive plane selectivity while forming their surface segregation layers (SSLs). The Ni‐SSL features a spinel‐like structure, while Co‐SSL is characterized as rock‐salt structure. The SSL shows dependence on the composition and synthesis methods, signifying a rational design of layered lithium transition‐metal oxide cathodes for optimized battery cycling stability.